A Survey on Early Size Estimation Techniques - Attri, Varinder Kaur; Singh, Jatinder (International Journal of Computer Sciences and Engineering, 2018)
Estimations play a very crucial role in the efficient termination of the task in software development life cycle (SDLC). Incorrect estimations hamper the progress of the project. As software estimation plays a critical role to control the project failures rate, estimation in the beginning of the software life cycle turns out to be very important goal for the software engineering community. For the effective development of the software project, early size estimation is considered an important parameter as it is essential for estimating the cost and total development effort. Earlier estimation leads to better project management .The main objective of this article is to explore the present literature with an intention to gain familiarity with the situation to examine the software estimation model and techniques. These estimation model and techniques helps in estimating the software size during the early phase of SDLC and acknowledge the gaps in the literature for future directions.